Entrepreneurship education in humanities and Social Sciences: are students qualified to start a business? - Vázquez-Burgete, José Luis; Lanero, Ana; Raisiene, Agota Giedre (Business: Theory and Practice, 2012)
Over the last decade, entrepreneurship education has been acknowledged by European governments as a promising way to improve the work insertion of young people and, at the same time, contribute to general purposes of social and economic welfare. Particularly, social entrepreneurship is considered an emerging area of growth which provides the opportunity to make a difference in global community contexts. From this view, this paper proposes a model of entrepreneurship education based on the European Framework on Key Competences for Lifelong Learning to analyze the involvement of universities in related actions as perceived by students within Humanities and Social Sciences. Data was collected from a total sample of 448 students at two Spanish universities. Descriptive analysis was used to examine the development of entrepreneurship-related knowledge, skills and attitudes among students and its implications for labor insertion of future graduates in Humanities and Social contexts. Further conclusions of the study are discussed.